2020
DOI: 10.1038/s41598-020-77099-7
|View full text |Cite
|
Sign up to set email alerts
|

Carbonization and H3PO4 activation of fern Dicranopteris linearis and electrochemical properties for electric double layer capacitor electrode

Abstract: Today, the world’s climate change is a growing problem, plant carbon sequestration is one of the effective ways to mitigate climate change by reducing greenhouse gases, mostly carbon gases. Dicranopteris linearis (D. linearis), a common fern species in the tropic or subtropic ecoregions, has been recently recognized as a potential feedstock to produce highly porous biochar. This study aims to enhance the specific surface area (SSA) and pore volumes of biochars derived from the D. linearis by H3PO4 activation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Compared with various D. linearis- derived chars from different pyrolysis techniques in our previous studies, which showed their SSA values in the range from 40 to 524 m 2 g −1 , the CO 2 /steam-activated chars expressed a much higher SSA 22 . More interestingly, the performance of CO 2 and steam in boosting SSA was at least equal to that of H 3 PO 4 28 , and this finding is well aligned with previous studies using the same method 29 , 30 .…”
Section: Resultssupporting
confidence: 89%
“…Compared with various D. linearis- derived chars from different pyrolysis techniques in our previous studies, which showed their SSA values in the range from 40 to 524 m 2 g −1 , the CO 2 /steam-activated chars expressed a much higher SSA 22 . More interestingly, the performance of CO 2 and steam in boosting SSA was at least equal to that of H 3 PO 4 28 , and this finding is well aligned with previous studies using the same method 29 , 30 .…”
Section: Resultssupporting
confidence: 89%
“…Figure 6 illustrates a distinct increase in electrochemical capacity of the A-xKC samples, characterized by rectangular CV shapes and triangular GCD shapes, both typical of Electric Double-Layer Capacitor (EDLC) electrode materials (Trinh et al 2020). A-xKC had a capacitance of both CV and GCD greater than 160 F g − 1 , which is considered better than biochar prepared from some bark materials such as willow bark (Hobisch et al 2020), tree bark (Momodu et al 2017).…”
Section: Electrochemical Performancementioning
confidence: 99%
“…Tis optimization process was intended to produce high biochar yields and specifc surface area. About 30 g of powdered leaves was impregnated with H 3 PO 4 (85% w/w, Merck) at the ratio of 1 : 1 with diferent acid concentrations (25%, 55%, and 85%) for 24 h and heated in an oven at 60 °C [23]. Tis impregnation ratio was taken constantly throughout the experiment.…”
Section: Adsorbent Preparation Te Leaves Of Cordia Africanamentioning
confidence: 99%